The Project Hospital Specialist Of Orthopedic And Traumatology - Endi Martha Mulia; Syamsulsyah Lubis; Jefri (CV. Inara, 2021)
Orthopedics is a branch of medicine that studies various functions and disorders that can occur in the musculoskeletal system. WHO reports that musculoskeletal disorders are the second most common disease worldwide after influenza. In North Sumatra, the prevalence of joint disease in populations over 15 years is 5.4% (around 778,500 people). While traumatology is a subspecialist of orthopedics specializing in dealing with injuries due to accidents or violence and surgical treatment. Indonesia is reported to have increased the number of traffic accidents in 2018 by 10% from the previous year with 25,000-30,000 victims. From the data above, the need for orthopedic and traumatology health services is high, but in Indonesia there are only 3 orthopedic and traumatology specialist hospitals. In North Sumatra, there are no orthopedic and traumatology specialist hospitals yet, so the idea of planning and designing an Orthopedic and Traumatology Specialist Hospital with facilities that support the management of patients with diseases related to the musculoskeletal system and wound management both caused by musculoskeletal disorders and caused by accidents and violence.